2020
DOI: 10.21118/apgs.v12i2.6011
|View full text |Cite
|
Sign up to set email alerts
|

Quando o Desastre Bate à Porta: Reflexões sobre a Ética da Gestão Pública de Riscos e de Desastres

Abstract: O aumento na ocorrência de tragédias em todo o mundo exige que governo e sociedade atuem na gestão integrada de riscos e de desastres, reforçando a importância desse tema em diferentes níveis do poder público nos quais questões éticas muitas vezes se manifestam. Considerando esse contexto, o objetivo deste artigo teórico foi realizar uma reflexão sobre a ética da gestão pública de riscos e de desastres. Foi enfatizada a ética dos desastres como elemento indispensável para a gestão de emergências, evidenciando … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…The topics that guided the search for cases in the Brazilian public management analyzed in this study were selected based on the suggestions found in the literature on ethics and emergency management to identify moral dilemmas (Aung et al, 2017;Geale, 2012;Santos & Serafim, 2020). The topics were 'triage, ' 'relief funds, ' 'risk communication, ' 'professional support, ' 'resource allocation, ' 'linguistic, religious, and cultural differences, ' 'vulnerable groups, ' 'surveillance of communicable diseases, ' and 'lockdown/social distancing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The topics that guided the search for cases in the Brazilian public management analyzed in this study were selected based on the suggestions found in the literature on ethics and emergency management to identify moral dilemmas (Aung et al, 2017;Geale, 2012;Santos & Serafim, 2020). The topics were 'triage, ' 'relief funds, ' 'risk communication, ' 'professional support, ' 'resource allocation, ' 'linguistic, religious, and cultural differences, ' 'vulnerable groups, ' 'surveillance of communicable diseases, ' and 'lockdown/social distancing.…”
Section: Methodsmentioning
confidence: 99%
“…Within this context of collective and individual actions, ethical tensions emerge as conflicts, motivated by a) different values and objectives (Aung, Rahman, Nurumal, & Ahayalimudin, 2017), b) limited and scattered information, c) multiple demands, and d) scarcity of resources (Santos & Serafim, 2020). These tensions lead to moral dilemmas that are more evident, making the ethical decision more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Risk management -acting in a preventive manner -is as important or more important than managing the disaster itself, that is, acting when the disaster occurs (Santos & Serafim, 2020). The management of this type of event translates often into a large, complex, and prolonged operation which involves public and private organizations and is directly linked to the lives of citizens and the well-being of societies.…”
Section: Public Management and The Area Of Emergency Managementmentioning
confidence: 99%
“…The characteristic found in challenges presented by crises and disasters and the way they differ from everyday situations require preventive reflection that prepares public management for the many dilemmas tragedies impose (Santos, 2019;Santos & Serafim, 2020). Therefore, adequate knowledge about risk and disaster management in the public sector is essential, as well as analyses on the actions carried out in the context of public management, especially in a preventive and proactive manner, by public authorities.…”
Section: Public Management and The Area Of Emergency Managementmentioning
confidence: 99%
“…A gestão de riscos -a atuação de maneira preventiva -é tão ou mais importante que a gestão do desastre propriamente dito, ou seja, a atuação quando o desastre ocorre (Santos & Serafim, 2020). A gestão desse tipo de evento é muitas vezes uma operação de grandes proporções, complexa e prolongada, que envolve organizações públicas e privadas e "está diretamente ligada à vida dos cidadãos e ao bem-estar das sociedades.…”
Section: Gestão Pública E a áRea De Proteção E Defesa Civilunclassified